Distorsi Keterwakilan Perempuan Melalui Pasal 8 ayat (2) PKPU Nomor 10 Tahun 2023 - Ogie Nuggraha; Durohim Amnan (Jurnal Hukum dan Sosial Politik, 2023)
Issuance of General Election Commission Regulation Number 10 of 2023 concerning the Nomination of Members of the DPR, Provincial DPRD and Regency/City DPRD, special wabil Article 8 paragraph (2) raises a new polemic because it is felt to deny the value of the struggle for democracy and the rule of law principle which has been painstakingly built so far sucks. The regulation is considered to reduce and distort the instrument of struggle for women's groups known as the affirmative action quota for women's representation of 30% in Parliament. The purpose of this study is to describe the problems that occur and discuss them in depth through methodological analysis. The research method that the author uses in this work is normative-juridical research with a library research approach which is coupled with gender theory and democratic principles and which is linked to the theme of this research discussion and uses qualitative methods. Research results Based on the description above, the authors conclude that Article 8 paragraph (2) PKPU 10/2023 is contrary to the principles of non-discrimination and the substantive equality and justice approach because it is not in line with the spirit of The Convention on the elimination of All Forms of Discrimination against Women (CEDAW ) which is further regulated in Law no. 7/1984 concerning the Convention on the Elimination of All Forms of Discrimination Against Women. Furthermore, the PKPU is not in line with the idea of ​​equality contained in the body of the 1945 Constitution of the Unitary State of the Republic of Indonesia such as Article 27 paragraph (1), Article 28D paragraph (3), Article 28H paragraph (2), and Article 28I paragraph (2). Article 8 paragraph (2) PKPU 10/2023 does not follow up on the essence of the legal norms of Article 245 Law Number 7 of 2017 concerning General Elections.